(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: In developing countries, nosocomial transmission of blood borne infection is terrific hinderance, largely due to reduced resources, limited education on infection control and fewer enforcement structures. Aims: The present study aimed to provide information on the level of awareness, knowledge, and attitude among medical and paramedical students as well as the health care workers about blood borne infections. Methods: This prospective cross-sectional study included a total of 449 participants. Out of which 177 (39.42%) were medical students, 103 (22.94%) were paramedical students and 169 (37.64%) were health care workers of tertiary care hospital, Anand. Pre-validated Google form questionnaire consisting of three sections were used to assess the knowledge and awareness about blood borne infections. Result: The results of present study shows that the knowledge and awareness regarding section I (General precautions to be taken) and section II (mode of transmission, signs, and symptoms) were statistically significant (p value: 0.000) and very poor hence need more educational programs to be conducted to increase the level of significance. Conclusion: The present study concludes the need of the educational programs on universal precaution to increase awareness and also to build up positive attitude towards blood borne infections. It will help in reducing the risk of transmission in the students as well as healthcare professionals and will improve knowledge, skills, and competency in treating infected patients.